Infection Rates in Open Fractures of the Tibia: Is the 6-Hour Rule Fact or Fiction? - Ameya S. Kamat (Advances in Orthopedics)
Aims. Emergency debridement has long been the standard of care for open fractures of the tibia as infection is an important complication. The timing of operative debridement can be debated. We review open fractures of the tibia and compare infection rates in those that were operated on within and after 6-hours. Method. 103 consecutive open fractures of the tibia were reviewed. The data was analysed retrospectively with regard to severity of fracture and incidence of infection. Infection rates over a three-month period were compared between the two groups. Results. 12 (11.6%) patients developed an infection within the first 3 months of injury. 7 of which were taken to theatre within 6-hours, and 5 after 6-hours. No significant differences were found between these two groups. Conclusion. There is no significant difference in timing of surgery. Initial basic interventions may play more of a role in limiting the risk of infection.